Efferent Reader Response Study on Adrian Lyne’s Lolita Movie - Yolanda Tesalonika Danta (Surakarta English and Literature Journal, 2024)
This study examines reader responses to a Lolita movie by Adriane Lyne based on the problem of how people interpret and retain pros and cons in the movie. How viewers' moral frameworks and ethical considerations influence their reader responses to the moral themes depicted in the movie "Lolita." How viewers’ perceptions of the characters, themes, and events in “Lolita” influence their efferent responses to the movie. This study applies the efferent reader response theory by Louise Rosenblatt. The data of this research consists of several comments and opinions of the viewer of the Lolita movie directed by Adrian Lyne that discussed the contradiction between the theme of pedophilia and its cinematography. The primary data are collected from the sources around the reader's opinion of the movie. Meanwhile, secondary data are obtained from other resources, such as related previous studies, journals, and other sources. Data collection are accomplished through the use of document analysis.The audience's reaction to Lyne's "Lolita" was divided, with 113 out of 173 approving it as a significant adaptation for its novel authenticity and quality, while 60 criticized it for its explicit and provocative portrayal of relationships, deeming it too far from the original novel while Viewers' moral attitudes significantly impact their understanding of Lyne's "Lolita," which questions society conventions and ethical standards by addressing controversial topics like as knowledge, exploitation, and the complexity of human sexuality.